Minority Stress and Positive Identity Aspects in Members of LGBTQ+ Parent Families: Literature Review and a Study Protocol for a Mixed-Methods Evidence Synthesis - Magdalena Siegel; Muriel Legler; Fortese Neziraj; Abbie E. Goldberg; Martina Zemp (Children, 2022)
Background: Parents and children in LGBTQ+ parent families face unique stressors (i.e., minority stress), but also possess unique resources (i.e., positive identity aspects) related to their family identity. Empirical evidence and theory suggest that these minority stressors and positive identity aspects are situated on the individual, couple, and family level and may be associated with key outcomes, including parent and child health, family functioning, and school-related outcomes. A systematic evidence synthesis and a theoretical placement are currently lacking. The aims of the systematic review outlined in this protocol are thus to (1) map minority stressors and positive identity aspects according to multiple levels in the family system, and (2) to synthesize evidence on their associations with key outcomes. Methods: We will conduct a PRISMA-conform mixed-methods systematic review. Studies will be retrieved using a multi-tiered search strategy, including database searches (PsycInfo, PubMed, Scopus, Web of Science), cited literature searches, authors’ publication lists, and study requests. The mixed-methods synthesis will follow a parallel-results convergent synthesis design, where quantitative results will be synthesized via meta-analysis and qualitative results via thematic synthesis. Conclusions: Our proposed systematic review may add to the theoretical understanding of LGBTQ+ parent family functioning and advance social inclusion of LGBTQ+ parent families.